Uwagi o porównywaniu koncepcji nauczania literatury = The remarks on comparing the conceptions of literature teaching - Biłos, Edward (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The paper deals with the problem of comparing the conceptions from the point of view of teaching the culture.
Keywords: dydaktyka literatury; koncepcje